2010
DOI: 10.1136/hrt.2010.200709
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults with congenital heart disease: biopsychosocial determinants and sex-related differences

Abstract: In ACHD, female gender was associated with poor physical and psychological QoL. The common denominators for QoL were primarily personality trait, psychological distress and family support, but not disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 24 publications
8
52
2
1
Order By: Relevance
“…This phenomenon can be accommodated by a higher financial independence, by the guarantee of social security, by the improvements in the level of education in the last decades, and by greater access to health care services. 42 HFD remained associated with AMI, suggesting that, in the disease's acute stage, physical worsening, absence or lack of family support, and psychological stress may influence family functionality quality. 42 In relation to chronic non-communicable diseases, the level of family dysfunction is shown to be significant for other health conditions, such as controlling and living with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon can be accommodated by a higher financial independence, by the guarantee of social security, by the improvements in the level of education in the last decades, and by greater access to health care services. 42 HFD remained associated with AMI, suggesting that, in the disease's acute stage, physical worsening, absence or lack of family support, and psychological stress may influence family functionality quality. 42 In relation to chronic non-communicable diseases, the level of family dysfunction is shown to be significant for other health conditions, such as controlling and living with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…42 HFD remained associated with AMI, suggesting that, in the disease's acute stage, physical worsening, absence or lack of family support, and psychological stress may influence family functionality quality. 42 In relation to chronic non-communicable diseases, the level of family dysfunction is shown to be significant for other health conditions, such as controlling and living with diabetes. In these people, controlled glycemic levels were linked to better family functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the difference in reported prevalence of snoring between genders, there was no interaction between gender and MSG intake. 25 The main limitation of this study is the use of self-reported sleep data instead of the more valid polysomnographic method to confirm the diagnosis of SDB. However, questionnaires have previously been found to be useful and are widely accepted in detecting and screening for SDB in large epidemiological studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) has been found to be associated with OSA [23] A study in Shanghai showed that the prevalence of GERD in adults, defined as heartburn and/or regurgitation of any frequency during the previous week, was 6.2% [24]. Several largepopulation studies in China found an association between GERD and sleep disorders [25]. Heartburn is a common complaint in relation to the "Chinese Restaurant Syndrome" [26] and given the effects of MSG on gastro-intestinal motility it possible that increased reflux is a mediating factor.…”
Section: Discussionmentioning
confidence: 99%